MOOCs對高等教育教學之挑戰與問題 Challenges and Issues Related to Massive Open Online Courses in Higher Education Teaching and Learning - 侯雅雯 Ya-Wen Hou (Higher Education Foundation, 2017)
近期高等教育崛起一股新興風潮，是強調大規模、開放、自我進度學習與共 享之「大規模開放線上課程」（MOOCs，臺灣稱為「磨課師」）。MOOCs被認為 是將教育機會擴展至全球學習者的一種方式，但此風潮卻引起許多批評。因此， 本文主要探討MOOCs之發展及其對高等教育領域之影響。透過文獻分析，本文先 討論MOOCs之起源與特性，並概述三大MOOCs平臺公司─Udacity、Coursera與 edX；最後，討論此風潮所引發的挑戰，包含MOOCs之定義、中輟率、課程建議、 互動品質、學位授予、全球競爭、教育商品化與智慧財產權等議題。 An emerging trend for teaching and learning in higher education is massive open online courses (MOOCs), which emphasize massiveness, openness, self-paced learning, and sharing. MOOCs are considered as an approach to expanding educational opportunities for learners in the globe, while some criticism of MOOCs emerges. The article aims to explore the development of MOOCs and their impacts in the field of higher education. Through literature review, this article first discusses the origin and characteristics of MOOCs, and then delineates the three big MOOCs providers─Udacity , Coursera, and edX. Finally, the challenges in relation to the MOOCs trend are discussed.